Influence of Social Media and Graffiti on Behaviours of Secondary School Students as expressed by Teachers in Osun State, Nigeria - Idowu, A. O.; Esere, M. O.; Idowu, A. I.; Ajiboye, T. A. (NIU Journal of Humanities, 2017)
Social media are platforms which students use for online interactions, while graffiti is an act of painting or writing on a surface illicitly. This research study investigated influence of social media and graffiti on behaviours of secondary school students as expressed by teachers in Osun State, Nigeria. Descriptive survey design was adopted for the study, while random and stratified sampling technique ware adopted to draw a total sample of 375 secondary school teachers in the three senatorial districts in Osun State. A self-developed instrument entitled â€œInfluence of Social Media and Graffiti on Behaviour Questionnaireâ€ was used to collect relevant data. The instrument has a co-efficient of 0.65 using test re-test reliability method. The major findings of the study revealed that social media has more negative influence on adolescentsâ€™ behaviour than the positive side of it because adolescentsâ€™ involvement in the use of social media usually result to wastage of time through chatting, pinging, making false statements, watching pornographic films/videos and involvement in cyber terrorism. The study also revealed that studentsâ€™ involvement in graffiti influence their behaviours negatively as it encourages them to harass their colleagues, vandalize public and private properties, and form bad gangs. In line with findings of this study, it is recommended that counsellors should educate parents on the necessity of discussing internet and cell phone safety with their children, parents should provide information specifically on safe and respectful uses of technology, students should be well informed of the dangers and the devastating effects of social media and graffiti abuse, school teachers should expose students to the danger inherent in negative uses of social media and graffiti and they should also relate with the school counsellors and parents on ways by which social media and graffiti could be used to channel the behaviours of adolescents towards positive activities. Keywords : social media, graffiti, behavior, secondary school students